2014
DOI: 10.1002/app.40507
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion failure of antiscratch coatings on polycarbonate under UV irradiation

Abstract: The adhesion failure of antiscratch (AS) coatings on unmodified and plasma-modified polycarbonate (PC) substrate was studied using both chemical and physical methods while considering the surface and interface changes between coatings and PC under ultraviolet (UV) irradiation. The differences in the wettability and surface elemental compositions of the PC surface (PCs) and AS coatings after UV ageing were evaluated by contact angle and Fourier transform infrared (FTIR) measurements. The nanoindentation techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The properties of PC/S, UVC-PC/S, and Nano-PC/S samples were compared comprehensively to investigate the advantages of coating on the nanostructured surface over conventional coating on a flat surface and activated surface (UVC treated surface) (Figure a). The cross-sectional images are shown in Figure b; it was found that the PC/S sample displayed an obvious interfacial gap due to the modulus and surface energy mismatch between PC and silicone . The interfacial gap is significantly mitigated on the UVC-treated PC surface because of the enhanced surface energy of PC (c.f.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of PC/S, UVC-PC/S, and Nano-PC/S samples were compared comprehensively to investigate the advantages of coating on the nanostructured surface over conventional coating on a flat surface and activated surface (UVC treated surface) (Figure a). The cross-sectional images are shown in Figure b; it was found that the PC/S sample displayed an obvious interfacial gap due to the modulus and surface energy mismatch between PC and silicone . The interfacial gap is significantly mitigated on the UVC-treated PC surface because of the enhanced surface energy of PC (c.f.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the contrary, Nano-PC/S still maintained a smooth surface. The cracking of coatings was mainly caused by the stress generated during UV irradiation due to the UV-induced mismatching of mechanical properties of the coating material and substrate material . The concentration of stress in long-time UV exposure will lead to cracking or detachment of the coating layer.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleaned PC plates were modified under the Ar/oxygen plasma generated by a gridless ion beam source with low energy. Additional details about this process can be found in our work . Prior to pretreatment, the reactor was vacuumed to a base pressure below 3 × 10 −3 Pa.…”
Section: Methodsmentioning
confidence: 99%
“…Commercially available 1 mm thick PC sheets (GE9030, General Electric co., USA) were rinsed with neutral detergent, ethanol, and distilled water, then dried at 70 °C for 1 h before surface pretreatment. The silicone coating material was prepared using sol–gel methods . An initial solution was prepared by mixing acid‐silica, methyltriethoxysilane (MTES), and tetrothoxysilane (TEOS) using HCOOH as catalyst.…”
Section: Methodsmentioning
confidence: 99%